Propostas de melhoria na gestão do programa de pós-graduação em gestão de organizações públicas a partir dos critérios definidos pela Capes - Machado, Vanessa Dutra (2021)
This study aims to propose suggestions for management improvements in the postgraduate program Public Organizations Management (PPGOP) based on CAPES Evaluation System. The methodology is classified as qualitative in terms of nature, as descriptive in terms of research objective and as a case study in terms of research strategy. Data collection was developed in two stages in which, first, data were collected through Sucupira Platform and also through the documents that make up the curricular structure of the unit of analysis; then, the analyzes and later results were carried out. The data were treated by descriptive analysis. As for the results, we observed that the PPGOP is moving towards a higher assessment than the one it currently maintains, the analyzed triennium, and, compared to courses with higher grades, it demonstrates that, in several sectors, it has been improving and developing actions that lead to the improvement in the program grade. PPGOP stands out for presenting research lines structured in a significant number, evolution in offering diverse subjects and a highly qualified faculty, besides being the only postgraduate program in professional master’s degree in southern Brazil. On the other hand, it faces challenges, such as little financial incentive, and the attempt to develop the internationalization of the course, which is still weak today. Therefore, the proposed final product is called an action plan with suggestions for improvement according to criteria defined by CAPES, in which there are several planning and organization methodologies for implementing them.